PENGARUH TERPAAN BERITA EFEK VAKSIN COVID-19 DI INSTAGRAM @DETIKCOM TERHADAP PERSEPSI REMAJA DI KOTA DENPASAR TENTANG VAKSIN COVID-19 (E-Jurnal Medium, 2022)
Instagram account @detikcom consistently uploads news about the effects of the COVID-19 vaccine which always attracts the attention of netizens on Instagram. The exposure to the news about theside effects of the COVID-19 vaccine then gave rise to various perceptions for the public about the COVID-19 vaccine. The purpose of this study is to explain the influence of news of the effects of the COVID-19 vaccine on Instagram @detikcom. The sample of this study was 210 using non-probability sampling technique, namely purposive sampling. Data collection through questionnaires.The analysise technique used is simple linear regression. News of the effect of the COVID-19 vaccine on Instagram @detikcom has a positive and significant impact on the perception of teenagers in Denpasar City. When the news of the effect of the COVID-19 vaccine on Instagram @detikcom increases, the perception of teenagers in Denpasar City will also increase. Keywords : News Exposure of the COVID-19 Vaccine Effect, Instagram @detikcom, Teenagers Perception